2008
DOI: 10.3141/2088-01
|View full text |Cite
|
Sign up to set email alerts
|

Microsimulation Calibration Using Speed-Flow Relationships

Abstract: A microsimulation calibration methodology based on matching speed-flow graphs from field and simulation is presented. Evaluation and automation of matching speed-flow graphs are based on methods from pattern recognition. The methodology was applied to the US-101 freeway network in San Francisco, California, by using an evolutionary algorithm. The methodology is compared to traditional methods of calibration based on capacity and is shown to perform better. In addition, a small-scale test-network simulation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…According to comprehensive literature reviews (Lee and Ozbay, 2009;Lee et al, 2013;Menneni et al, 2008), prior methods offer a limited set of output parameters for calibration. By contrast, SASCO architectures allow any simulation output value, or distribution (Kim et al, 2005) of values, to be used for calibration.…”
Section: Output Data User-interfacementioning
confidence: 99%
See 1 more Smart Citation
“…According to comprehensive literature reviews (Lee and Ozbay, 2009;Lee et al, 2013;Menneni et al, 2008), prior methods offer a limited set of output parameters for calibration. By contrast, SASCO architectures allow any simulation output value, or distribution (Kim et al, 2005) of values, to be used for calibration.…”
Section: Output Data User-interfacementioning
confidence: 99%
“…Several of the papers cited by Lee and Ozbay (2009), Lee et al (2013), Menneni et al (2008) investigated SO-based calibration via genetic algorithms (GA) (Foy et al, 1992). GA is a well-known, intelligent heuristic searching method.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of using VISSIM over other contemporary software is that the model allows calibration of several parameters that encompass the driver's behavior in order to realistically replicate local traffic conditions. VISSIM is based on a psychophysical car-following model and uses perception thresholds to model driver behavior [25][26][27]. The enhanced functionalities of VISSIM compared to other simulation tools for analysis of different transportation problems have been demonstrated by a few previous studies [28,29].…”
Section: Selection Of Simulation Modelmentioning
confidence: 99%
“…Park and Won (2006) described a procedure for calibration of default parameters in VISSIM and found that the safety distance reduction factor defined for the link indicates the aggressiveness of the driver. Menneni et al, (2008) also performed the parameter calibration of VISSIM using optimization algorithm and developed a new methodology for assessing the capacity by matching the speed-flow graphs from the field as well as from simulation. Park and Kwak (2011) also evaluated the results of calibration and validation procedure by comparing the distribution of simulation output with field data.…”
Section: Studies Based On Simulationmentioning
confidence: 99%